Major constituents of Cistanche tubulosa, echinacoside and acteoside, inhibit sodium-dependent glucose cotransporter 1-mediated glucose uptake by intestinal epithelial cells. (December 2017) - Shimada, Hiroaki; Urabe, Yuichi; Okamoto, Yuhei; Li, Zheng; Kawase, Atsushi; Morikawa, Toshio; Tu, Pengfei; Muraoka, Osamu; Iwaki, Masahiro
Highlights: SGLT1-mediated glucose uptake in Caco-2 cells can be evaluated by using 2-NBDG. ECH and ACT inhibited SGLT1-mediated 2-NBDG uptake more strongly than phlorizin did. The inhibitory mechanism of C. tubulosa on dietary glucose absorption was indicated. Abstract: Echinacoside (ECH) and acteoside (ACT), the major constituents of Cistanche tubulosa, suppress the increase in postprandial blood glucose level. Although ECH and ACT have been reported to weakly inhibit α-glucosidases, the underlying mechanism remains unclear. Therefore, we focused on the regulatory mechanism of dietary glucose absorption. In this study, we aimed to clarify the inhibitory effects of ECH and ACT on sodium-dependent glucose cotransporter (SGLT) 1-mediated gastrointestinal glucose absorption. Uptake experiments were performed using human intestinal Caco-2 cells and the fluorescence glucose analogue, 2-deoxy-2-[(7-nitro-2, 1, 3-benzoxadiazol-4-yl)amino]-d -glucose (2-NBDG). Sodium-dependent 2-NBDG uptake was successfully estimated and this uptake was completely inhibited by an SGLT inhibitor phlorizin. ECH and ACT inhibited sodium-dependent 2-NBDG uptake in a concentration-dependent manner. However, this inhibition was not observed under sodium-free condition. This study suggested that the inhibitory effects of ECH and ACT on SGLT1-mediated glucose uptake contribute to suppression of increased postprandial blood glucose level.